Teaching NeuroImage: Nitromethane-Induced Acute Reversible Encephalopathy. (28th September 2021) - Palumbo, Giovanni; Besana, Michele; Ananiadou, Sofia; Giordano, Carolina; Maccabelli, Gloria; Riccio, Mario; Campana, Chiara; Giossi, Alessia; Piovan, Enrico; Lonati, Davide; Pinelli, Lorenzo
Abstract : A 60-year-old man presented to the emergency department reporting that he accidently swallowed a sip (about 20 mL) of nitromethane he used as fuel for his racing bikes. Over the following 2 days, he became stuporous, experienced tonic-clonic seizures, and ultimately fell into a coma. Brain MRI showed multifocal gray matter T2/fluid-attenuated inversion recovery hyperintensities consistent with previously published findings of acute nitromethane encephalopathy 1 (Figure 1, A and B). After 1 week, the follow-up MRI showed massive vasogenic brain edema (Figure 1, C and D). Nonetheless, the patient's condition was improving with supportive therapy only. One month after his admission, he was back to baseline and he was discharged; 6 months later, brain MRI was normal (Figure 2).